Assessing the adoptability of limestone calcined clay cement (lc3) in slab-like elements - Abdrafiu, Idris Mayowa (Stellenbosch : Stellenbosch University, 2025)
CITATION: Abdrafiu, I.M. 2025. Assessing the Adoptability of Limestone Calcined Clay Cement (LC3) in Slab-like Elements. Unpublished masters thesis. Stellenbosch: Stellenbosch Univeristy [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131995